Statistical subspace-based damage detection with estimated reference. (1st February 2022) - Viefhues, Eva; Döhler, Michael; Hille, Falk; Mevel, Laurent
Abstract: The statistical subspace-based damage detection technique has shown promising theoretical and practical results for vibration-based structural health monitoring. It evaluates a subspace-based residual function with efficient hypothesis testing tools, and has the ability of detecting small changes in chosen system parameters. In the residual function, a Hankel matrix of output covariances estimated from test data is confronted to its left null space associated to a reference model. The hypothesis test takes into account the covariance of the residual for decision making. Ideally, the reference model is assumed to be perfectly known without any uncertainty, which is not a realistic assumption. In practice, the left null space is usually estimated from a reference data set to avoid model errors in the residual computation. Then, the associated uncertainties may be non-negligible, in particular when the available reference data is of limited length. In this paper, it is investigated how the statistical distribution of the residual is affected when the reference null space is estimated. The asymptotic residual distribution is derived, where its refined covariance term considers also the uncertainty related to the reference null space estimate. The associated damage detection test closes a theoretical gap for real-world applications and leads to increased robustness of the method in practice. The importance of including the estimation uncertainty of the reference null space is shown in a numerical study and on experimental data of a progressively damaged steel frame. Highlights: An output covariance Hankel matrix is confronted to its left reference null space in damage residual. The residual distribution is derived, also considering estimation uncertainties of the reference. Thresholds for early damage detection can be defined precisely a priori. The resulting detection test has increased performance in particular for short reference data. The method is applied to experimental data under small damage and for short data.